2017
DOI: 10.1080/02701367.2017.1408951
|View full text |Cite
|
Sign up to set email alerts
|

Entering the Field of Physical Education: The Journey of Fifteen First-Year Teachers

Abstract: Implications indicate a need for purposeful physical education teacher education training to proactively address these barriers during professional preparation as well as the creation of additional support systems for beginning teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
11
0
2
Order By: Relevance
“…The performance of beginning physical educators is influenced by the diverse nature of each individual's unique first-year journey, and the art of learning to teach is highly dependent on the availability of adequate resources, support structures, internal motivation, the context of the learning environment, and other complex factors. Ensign et al (2018a) have identified enhancers, such as positive interactions with students and colleagues, and barriers, such as role conflict and problems with classroom management. By combining the theoretical perspectives of Bernstein and Bourdieu in their analysis, Aldous and Brown (2010) have further shown that it is crucial that the beginning PE teacher's habitus, based on early biography, teacher training, and experience of PE teaching is supported by the already established framing and performance codes of the school subject of PE.…”
Section: The Induction Phase Of Pe Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of beginning physical educators is influenced by the diverse nature of each individual's unique first-year journey, and the art of learning to teach is highly dependent on the availability of adequate resources, support structures, internal motivation, the context of the learning environment, and other complex factors. Ensign et al (2018a) have identified enhancers, such as positive interactions with students and colleagues, and barriers, such as role conflict and problems with classroom management. By combining the theoretical perspectives of Bernstein and Bourdieu in their analysis, Aldous and Brown (2010) have further shown that it is crucial that the beginning PE teacher's habitus, based on early biography, teacher training, and experience of PE teaching is supported by the already established framing and performance codes of the school subject of PE.…”
Section: The Induction Phase Of Pe Teachingmentioning
confidence: 99%
“…Ensign et al (2018a) have identified enhancers, such as positive interactions with students and colleagues, and barriers, such as role conflict and problems with classroom management. By combining the theoretical perspectives of Bernstein and Bourdieu in their analysis, Aldous and Brown (2010) have further shown that it is crucial that the beginning PE teacher's habitus, based on early biography, teacher training, and experience of PE teaching is supported by the already established framing and performance codes of the school subject of PE.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, teachers' perceptions of poor pupil behaviour and the desire to manage such issues can result in whole-class progressive drills utilising reproductive teaching styles and closed questioning to ensure pupils stay busy, active and reduce discussion time (Curtner-Smith, Hastie and Kinchin 2008). Secondly, difficulties accommodating the variety of differing pupil abilities can also lead to the teacher-led approach of whole-class progressive drills (Ensign, Kulinna and Woods 2018). Such teacher controlled approaches are somewhat understandable given pupil responses are likely to be more observable in PE than other subjects and the obvious need to ensure safety in practical activities (Stidder and Hayes 2011;Templin, 1979).…”
Section: Influential Factors Upon Teachers' Pedagogical Practicesmentioning
confidence: 99%
“…Gu & Liu (2019), que confirmaron el importante rol que tiene la actitud de los estudiantes de cara a la EF a la hora de adquirir y fomentar comportamientos de vida activos. El punto común entre los estudios incluidos en esta categoría es que la EF debería inculcar el conocimiento, habilidades y actitudes para hacer posible la práctica de AF a lo largo de todo el ciclo vital (Ensign, Mays-Woods & Kulinna, 2018;Gaviria-Cortés & Castejón-Oliva, 2016;McEvoy et al, 2017;Sánchez-Oliva et al, 2014;Sutherland et al, 2015).…”
Section: Estudiantesunclassified
“…El profesorado novel analizado por Ensign et al (2018) coincidió en señalar, casi unánimemente, que el principal objetivo de la EF debe ser educar al alumnado para llevar a cabo un estilo de vida saludable a lo largo de todo el ciclo vital y dotar a estos de las habilidades necesarias para tal efecto. Loundsbery, Holt, Monnat, McKenzie & Funk (2014) llevaron a cabo un análisis para comparar la materia de EF con otros programas alternativos que se están aplicando en diferentes estados de los Estados Unidos, en concreto, el Junior Reserve Officer Training Corps (JROTC).…”
Section: Barnie Pleban and Lewis 2017unclassified